Agricultural mechanization and child labour in developing countries: Background study - Takeshima, Hiroyuki; Vos, Rob (Food and Agriculture Organization of the United Nations, 2022)
The FAO-IFPRI study, focuses on the use of tractors because they are among the most versatile farm mechanization tools and are universal power sources for all other driven implements and equipment in agriculture, with significant potential to replace animal draught power and human power, including children’s muscle power. Tractor use is typically also the first type of machine-powered equipment in use at lower levels of agricultural development, the context where most child labour is found. Mechanization is mostly assumed to reduce child labour, as it is expected to be labour saving in general. Yet, this is not always the case, as it has also been observed that the use of tractors and other machinery could increase children’s engagement in farm activities. This may be the case if, for instance, their use allows farms to cultivate larger areas, or if it leads to shifting chores of work from hired labor to family workers, e.g. for weeding edges of farmland not reachable by machinery. Evidence has been scant thus far, but the few available studies have mostly lent greater support to the hypothesis that mechanization reduces children’s productive engagement. Most available studies have focused on specific cases and based on scant data. The new FAO-IFPRI study provides a rigorous quantitative assessment for seven developing countries in Asia (India, Nepal and Viet Nam) and sub-Saharan Africa (Ethiopia, Ghana, Nigeria and Tanzania) based on comparable farm household survey data.